E-LEARNING BAHASA INDONESIA : SOLUSI INOVATIF UNTUK PENDIDIKAN DI ERA DIGITALISASI - Everhard Markiano Solissa; Mas'ud Muhammadiah; Yoga Karmizi; Al Ikhlas; Ratna Susanti; Abraham Manuhutu (IICLS (Indonesian Institute for Corporate Learning and Studies), 2024)
The development of technology in the digital era has brought significant transformation in various aspects of life, including education. Indonesian E-learning emerges as an innovative solution to support effective, flexible and inclusive learning. This platform allows students to learn anytime and anywhere, with various interactive features such as learning videos, quizzes and discussion forums. E-learning also provides opportunities for teachers to deliver materials creatively, increase student engagement, and facilitate the evaluation of learning outcomes. This research aims to examine the effectiveness of Indonesian e-learning in improving students' language competence, both in the aspects of reading, writing, listening, and speaking. With a qualitative descriptive analysis approach, the results show that the integrated use of e-learning can increase students' learning motivation, facilitate adaptive learning, and support the achievement of educational goals in the digitalization era.